Improving Safely Managed Fecal Sludge Management in Tabek Village Through a Community-Led Total Sanitation (CLTS) Approach - Gusmira; Zulkarnaini (Warta Pengabdian Andalas, 2026)
Ownership of sanitation facilities does not necessarily guarantee the achievement of safely managed sanitation if it is not accompanied by adequate fecal sludge management. This condition is still prevalent in Tabek Village, Dharmasraya Regency, where all households have septic tanks, yet none have ever been desludged, increasing risks of leakage, groundwater contamination, and environment-based diseases. This community service activity aimed to increase public awareness and commitment to safely managed sanitation through the community-led total sanitation (CLTS) approach. Participatory triggering based on participatory rural appraisal (PRA) included sanitation mapping, transect walks, fecal volume calculations, contamination route analysis, and social contracts. The activity involved 25 community representatives assisted by sanitarians from the local health center and health office. Results showed that 15 septic tanks lacked manholes, and none had been emptied due to limited knowledge and lack of information on desludging services. Visual and emotional triggering led to a collective commitment to desludge septic tanks between January and April 2026. This activity demonstrates that the CLTS approach is effective in shifting community paradigms from merely owning facilities to actively managing safe sanitation.